PERFORMANCE TESTING ANALYSIS OF BANDUNGTANGINAS APPLICATION WITH JMETER - Ekky Novriza Alam; Fitriyana Dewi (International Journal of Innovation in Enterprise System, 2022)
The bandungtanginas.id application was created to serve the needs of data collection on maternal and child health at every posyandu in the city of Bandung. This application is planned to be able to serve around 1,982 posyandu in the city of Bandung, around 10,000 users, who are expected to be able to access the bandungtanginas.id application. In the current condition of the application support infrastructure still has limitations in supporting the bandungtanginas.id application. With specifications that tend to be low, an improvement effort is needed through generating application usage scenarios so that the services provided can be optimally available using the existing infrastructure. This research focuses on analyzing the application performance by using load testing. This research has four stages: determining the test's purpose, creating a test scenario, carrying out scenario testing, and analyzing the results. The analysis will be carried out with the results of load testing experiments based on the scenarios that have been made. Test scenarios are made to obtain experimental data, last further analysis and conclusions will be made. Scenarios are created based on an estimate of the optimal number of users the application should serve. The test scenario will use a target user of between 10 – 200 users who are divided in five groups of load testing scenarios. From this trial, it will be seen how the performance of the bandungtanginas.id application for each scenario group that has been created. The result of this study showed that the best scenario for bandungtanginas.id application could serve users in the range of 30-50 users. It is obtained from the response time results, which show the average results are under 30 seconds according to the SLA (Service Level Agreement) standard for application users.